Effective Technologies for Preparing Children with Disabilities for Social Life in Conditions of Inclusive Education - Usarov, Jabbor Eshbekovich; Kodirova, Feruzakhon Usmanovna; Akhlan, Riksma Nurahmi Rinalti (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This article describes how the level of formation of personal  qualities in deaf, weak hearing children is determined not by hearing impairment, but in connection with acquired knowledge, skills, qualifications and life competencies through a complex of social influences.Through the foundational experimental and test work of the study, work aimed at preparing students for social life during the period of school education was established, professional competencies of educators, opportunities for students to receive information and transfer. "Why do you think deaf, weak hearing students are not ready to attend further education after graduation?"- 78% of the answers to the question stated that students do not have spoken speech, do not have enough necessary knowledge from the sciences, do not have a speech Reserve to acquire knowledge. Also listed are the lack of thorough work on teaching to exchange ideas in oral and written forms, and the lack of targeted cooperation between teachers and educators, and the complexity of the content of textbooks.